Rancang Bangun Alat Pengontrol Penyiram Tanaman Otomatis Menggunakan Sensor Kelembaban Tanah Di Area Pertanian - Deddy Prayama; Amelia Yolanda; Andi Wellyno Pratama (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
One of the factors causing the lack of agricultural productivity in Indonesia is the majority of farmers in Indonesia still rely on climate change in the processing of agricultural land. The Design of Automatic Plant Sprinklers Control Devices Using Soil Humidity Sensor in the Agricultural Area was created aimed at helping farmers in Indonesia to manage agricultural land without the need to manually water and see weather conditions. How it works This tool is by using Arduino as a brain movement tool and Soil Moisture Sensor to retrieve data from plants. Then the data that has been obtained by the tool will be sent to the web-based monitoring system using Ethernet Shield. The experimental results and implementation in the field shows that this prototype or prototype can work according to its function and purpose.